Prevalence of antimicrobial resistance among bacterial pathogens isolated from cattle in different European countries: 2002–2004 - Stärk Katharina; Greko Christina; Moreno Miguel; Amado Alice; Utinane Andra; Franco Alessia; Butaye Patrick; Meunier Danièle; Teale Christopher; Schroeter Andreas; Mevius Dik J; Hendriksen Rene S; et al. (Acta Veterinaria Scandinavica, 2008)
Abstract Background The project "Antibiotic resistance in bacteria of animal origin – II" (ARBAO-II) was funded by the European Union (FAIR5-QLK2-2002-01146) for the period 2003–2005, with the aim to establish a continuous monitoring of antimicrobial susceptibility among veterinary laboratories in European countries based on validated and harmonised methodologies. Available summary data of the susceptibility testing of the bacterial pathogens from the different laboratories were collected. Method Antimicrobial susceptibility data for several bovine pathogens were obtained over a three year period (2002–2004). Each year the participating laboratories were requested to fill in excel-file templates with national summary data on the occurrence of antimicrobial resistance from different bacterial species. A proficiency test (EQAS – external quality assurance system) for antimicrobial susceptibility testing was conducted each year to test the accuracy of antimicrobial susceptibility testing in the participating laboratories. The data from this testing demonstrated that for the species included in the EQAS the results are comparable between countries. Results Data from 25,241 isolates were collected from 13 European countries. For Staphylococcus aureus from bovine mastitis major differences were apparent in the occurrence of resistance between countries and between the different antimicrobial agents tested. The highest frequency of resistance was observed for penicillin. For Mannheimia haemolytica resistance to ampicillin, tetracycline and trimethoprim/sulphonamide were observed in France, the Netherlands and Portugal. All isolates of Pasteurella multocida isolated in Finland and most of those from Denmark, England (and Wales), Italy and Sweden were susceptible to the majority of the antimicrobials. Streptococcus dysgalactiae and Streptococcus uberis isolates from Sweden were fully susceptible. For the other countries some resistance was observed to tetracycline, gentamicin and erythromycin. More resistance and variation of the resistance levels between countries were observed for Escherichia coli compared to the other bacterial species investigated. Conclusion In general, isolates from Denmark, England (and Wales), the Netherlands, Norway, Sweden and Switzerland showed low frequencies of resistance, whereas many isolates from Belgium, France, Italy, Latvia and Spain were resistant to most antimicrobials tested. In the future, data on the prevalence of resistance should be used to develop guidelines for appropriate antimicrobial use in veterinary medicine.